The relationship between sociocultural adaptation and L2 pragmatic development during online study abroad - Tahir, Ismail; Hamzah, Aryati (Universitas Islam Negeri Banda Aceh, 2023)
Although several linguists have examined the studies on study abroad (SA), limited studies have focused on online study-abroad contexts. The current study investigates the production of pragmatic routine and its influence on online sociocultural adaptation during online study abroad. This study involved Indonesian students in English and Chinese-taught programs at Beihang University, China. As a mixed method, this study uses Vocabulary Knowledge Scale (VKS) and Sociocultural Adaptation Scale (SCAS) to measure the students’ pragmatic routines production and online sociocultural adaptation. VKS scale is used to investigate the expression categories, including expressions of thanking, requesting, complementing, and greeting. In addition, SCAS is also used to explore the students’ sociocultural aspects, cognitive aspects, and behavioral situations. As a result, the study shows that most Indonesian students enrolling in Chinese and English-taught programs tend to produce pragmatic routines even though the Chinese aspect is produced more than the English aspect. Furthermore, there is also a positive contribution to the production of pragmatic routine and its development influenced by sociocultural adaptation during online study abroad.